HUBUNGAN TINGKAT KECEMASAN PASIEN DENGAN KEPATUHAN DIET PADA PASIEN DIABETES MELLITUS DI RUMAH SAKIT UMUM MITRA MEDIKA MEDAN TAHUN 2018 - Dedi, Dedi (Jurnal Keperawatan Priority, 2019)
Diabetes is one of the four priorities for non-communicable diseases. In 2015 diabetic 415 million adults with diabetes, a 4-fold increase from 108 million in the 1980s. In 20140 it is estimated that the number will be 642 million people. This study aims to determine the relationship of anxiety level of patients with dietary adherence in patients with Diabetes Mellitus at Mitra Medika General Hospital Medan in 2018. This research use analytic survey research design with cross sectional approach using chi-square test. The population in this study was Diabetes Mellitus patients amounted to 49 respondents, while the sample is the total sampling of the entire population of 49 respondents. The type of data used is primary data, secondary data and tertiary data, while the analysis used is univariate analysis and bivariate analysis. From the results of this study with Parson Chi-square statistical test, showed that the P value of 0.014. Where the value is smaller than α value of 0.05, then there is a relationship between the anxiety levels of patients with dietary adherence in patients with Diabetes Mellitus at Mitra Medika General Hospital Medan. The conclusions in this study showed that there was a statistically significant relationship between the anxiety levels of patients with dietary adherence in Diabetes Mellitus patients at Mitra Medika General Hospital Medan. It is suggested to do more research about patient's anxiety level with diet compliance, by using different research location and research method.